2019
DOI: 10.1590/s1517-707620190002.0692
|View full text |Cite
|
Sign up to set email alerts
|

Sorbent system based on acetylated microfibrillated cellulose for remediation of oil aquatic environments

Abstract: The growth of oil exploration and transport in marine environments brings concern over potential environmental disasters caused by oil spills. Thus, various materials are being developed and studied in order to minimize environmental impacts caused by these oil spills. Among these materials, the use of sorbents has appeared as a great potential technique for the treatment of effluents, by separating and collecting oil in the aqueous medium. This work describes the development of a sorbent system based on acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…For three kinds of organic solvents with low viscosity, the absorption capacity increased with their density increasing. It indicated that the absorption capacity of the materials depended on the density and viscosity of organics, which was consistent with the reported results (Lu et al, 2019; Zimmermann, Zattera, & Santana, 2019). It was also found that solvents and oils could be desorbed from ZSSiOsp, the oil desorption efficiency of sponge for chloroform was got to 90.3%, while RSO was only 65.3% as it had high viscosity.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For three kinds of organic solvents with low viscosity, the absorption capacity increased with their density increasing. It indicated that the absorption capacity of the materials depended on the density and viscosity of organics, which was consistent with the reported results (Lu et al, 2019; Zimmermann, Zattera, & Santana, 2019). It was also found that solvents and oils could be desorbed from ZSSiOsp, the oil desorption efficiency of sponge for chloroform was got to 90.3%, while RSO was only 65.3% as it had high viscosity.…”
Section: Resultssupporting
confidence: 91%
“…In order to investigate the absorption capacity of ZSSiOsp, three kinds of organics were selected as targeted substrates. They were organic solvent, such as hexane, toluene (Tol) and chloroform, petroleum was consistent with the reported results (Lu et al, 2019;Zimmermann, Zattera, & Santana, 2019). It was also found that solvents and oils could be desorbed from ZSSiOsp, the oil desorption efficiency of sponge for chloroform was got to 90.3%, while RSO was only 65.3% as it had high viscosity.…”
Section: Absorption and Regeneration Performancesupporting
confidence: 88%
“…The reaction for cellulose fibers can be performed at a relatively high concentration. [ 91 ] Dried cellulose fibers can be modified with a solvent‐free process, in which reactant is used to disperse cellulose [ 81,82,86,87,92 ] or a gas‐phase reaction is performed. [ 89 ] Rojas and co‐workers proposed that the heterogeneous acetylation of wood fibers could weaken the interfibrillar hydrogen bonds, which facilitates nanofibrillation.…”
Section: Stage‐oriented Modification Of Nanocellulosesmentioning
confidence: 99%